Nutritional Predictors of Complications Following Radical Cystectomy - Johnson, David C. (World J Urol, 2014)
PURPOSE: To determine the impact of preoperative nutritional status on the development of surgical complications following cystectomy using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). METHODS: We performed a retrospective review of the NSQIP 2005–2012 Participant Use Data Files. ACS-NSQIP collects data on 135 variables, including pre- and intraoperative data and 30-day post-operative complications and mortality on all major surgical procedures at participating institutions. Preoperative albumin (<3.5 or >3.5 g/dl), weight loss 6 months before surgery (>10%), and BMI were identified as nutritional variables within the database. The overall complication rate was calculated and predictors of complications were identified using multivariable logistic regression models. RESULTS: 1,213 patients underwent cystectomy for bladder cancer between 2005–2012. The overall 30-day complication rate was 55.1% (n=668). While 14.7% (n=102) had a preoperative albumin <3.5 g/dL, 3.4% had >10% weight loss in the 6 months prior to surgery, and the mean BMI was 28 kg/m(2). After controlling for age, sex, medical comorbidities, medical resident involvement, operation year, operative time and prior operation, only albumin <3.5g/dl was a significant predictor of experiencing a postoperative complication (p=0.03). This remained significant when albumin was evaluated as a continuous variable (p=0.02) CONCLUSIONS: Poor nutritional status measured by serum albumin is predictive of an increased rate of surgical complications following radical cystectomy. This finding supports the importance of preoperative nutritional status in this population and highlights the need for the development of effective nutritional interventions in the preoperative setting.